2022
DOI: 10.3390/cancers14041005
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of the Spectrum and Therapeutics of Helicobacter pylori-Negative Mucosa-Associated Lymphoid Tissue Lymphoma

Abstract: Helicobacter pylori (HP)-unrelated mucosa-associated lymphoid tissue (MALT) lymphoma includes the majority of extragastric MALT lymphomas and a small proportion of gastric MALT lymphomas. Although the role of first-line antibiotics in treating HP-negative gastric MALT lymphomas remains controversial, HP eradication therapy (HPE)-like regimens may result in approximately 20–30% complete remission (CR) for patients with localized HP-negative gastric MALT lymphoma. In these patients, H. heilmannii, H. bizzozeroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 134 publications
(263 reference statements)
0
15
0
Order By: Relevance
“…Autoimmune diseases such as Sjogren’s syndrome, IgG4-related diseases, and obesity also increase the risk of primary MALT lymphoma[ 5 ]. Another possibility is infection with bacteria other than H. pylori , which could explain why the eradication of H. pylori can treat some H. pylori -negative MALT lymphomas[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune diseases such as Sjogren’s syndrome, IgG4-related diseases, and obesity also increase the risk of primary MALT lymphoma[ 5 ]. Another possibility is infection with bacteria other than H. pylori , which could explain why the eradication of H. pylori can treat some H. pylori -negative MALT lymphomas[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori eradication therapy is the first choice for treating gastric MALT lymphoma in H. pylori -infected patients, and even in H. pylori -negative patients, since H. pylori -negative patients have also been shown to respond to eradication therapy. 37 Yasuda et al . recently reported finding H. suis infection even in their patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that H. suis was the most common NHPH that infected human stomachs 13 . The H. suis infection leads to diseases such as gastric mucosa-associated lymphoid tissue (MALT) lymphoma, nodular gastritis, chronic gastritis, and peptic ulcer [14][15][16][17][18][19][20] . However, the above reports did not provide proof of H. suis or other NHPH infection because they only used PCR assay and did not isolate the bacteria or analyze the isolated bacteria's genome to identify the infecting bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Although a false-negative test cannot be completely ruled out, these results seem to indicate that other bacteria may be associated with the lymphoma development. Gastric MZL, for example, may occur in patients with infection from H. heilmannii or other helicobacter species, the eradication of which may lead to lymphoma regression [47]. Gut microbiota might also be implicated in some antibiotic-responsive H. pylori -negative gastric MALT lymphoma [47].…”
Section: Other Helicobacter Speciesmentioning
confidence: 99%